Best practice in environmental management of uranium mining. - Waggitt, P. (IAEA nuclear energy series ;, 2010)
This publication has been written to assist member states in the development of their uranium mineral resources. It sets out the basic tenets of best practice in terms of environmental management of uranium mining and processing operations from the viewpoint of both operators and regulators, and is accompanied by a collection of case studies from leading representatives in the global mining industry. Includes CD-ROM with papers presented at an IAEA technical meeting in Saskatoon, Canada, June 22-25, 2005.--Publisher's description.